2017
DOI: 10.1016/j.envpol.2017.06.035
|View full text |Cite
|
Sign up to set email alerts
|

PM 2.5 exposure in utero contributes to neonatal cardiac dysfunction in mice

Abstract: Objective Exposure of fine particulate matter (PM2.5) to pregnant dams has been shown to be strongly associated with adverse cardiovascular outcomes in offspring at adulthood, however, effects evident during neonatal periods are unclear. We designed this study to examine cardiac function of neonatal mice (14 days old) exposed to in utero PM2.5. Methods Pregnant FVB female mice were exposed either to filtered air (FA) or PM2.5 at an average concentration of 91.78 μg/m3 for 6h/day, 5 days/wk (similar to exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 57 publications
(53 reference statements)
0
9
1
Order By: Relevance
“…One possibility is that circulating cytokines could contribute to vascular injury caused by CAP; however, in past studies, we have not found changes in circulating cytokines such as TNF-α and IL-6 in the plasma from CAP-exposed mice ( 20 ). In contrast, our studies and investigations by others indicate that PM 2.5 exposure increases local inflammation in vascular and cardiac tissue ( 10 , 19 ). Another possibility is that circulating microparticles or exosomes could deliver cargo to the vasculature that contributes to pathology; few published reports have addressed this possibility ( 23 , 61 , 62 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One possibility is that circulating cytokines could contribute to vascular injury caused by CAP; however, in past studies, we have not found changes in circulating cytokines such as TNF-α and IL-6 in the plasma from CAP-exposed mice ( 20 ). In contrast, our studies and investigations by others indicate that PM 2.5 exposure increases local inflammation in vascular and cardiac tissue ( 10 , 19 ). Another possibility is that circulating microparticles or exosomes could deliver cargo to the vasculature that contributes to pathology; few published reports have addressed this possibility ( 23 , 61 , 62 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Acute PM 2.5 exposure increases the risk of myocardial infarction, arrhythmias, and stroke (2), whereas chronic exposure contributes to the development of hypertension, atherosclerosis, and diabetes (2,(4)(5)(6). In utero and early life exposure is associated with cardiac dysfunction and the induction of transcriptional as well as metabolic changes in cardiomyocytes (7)(8)(9)(10). Because PM 2.5 exposure affects several aspects of CVD, it is likely that it alters processes that are common to several manifestations of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exposure to PM 2.5 via air cell injection resulted in elevated heart rate and thickened right ventricular wall thickness in fertile chicken eggs . Abnormalities in cardiac structure and function in the offspring induced by PM 2.5 exposure during pregnancy were confirmed in FVB mice and Wistar rats. , Maternal exposure to PM 2.5 during pregnancy damaged offspring hearts and changed cardiovascular development-related genes in C57BL/6 mice …”
Section: The Aop On Pm25 Induced Cardiac Developmental Toxicitymentioning
confidence: 99%
“…Calcium-regulated contraction is significantly affected throughout development in progeny exposed to particulate matter during gestation. Assessment of 14-day-old progeny whose dams were exposed to PM 2.5 during gestation revealed decreased cardiomyocyte contractility through calcium dynamics, with changes to proteins involved in calcium flux in the heart, SERCA-2a, p-PLN, Na ϩ /Ca 2ϩ exchanger (NCX), calcium channel, voltage-dependent L type, and ␣1C subunit (CaV1.2) (149,150). Offspring whose dams were exposed during gestation also present with major cardiac anomalies present into adulthood as a result of ENM-induced mitochondrial dysfunction.…”
Section: Cellular Functionmentioning
confidence: 99%